Protocol for the “stand the future” trial: robotic exoskeleton gait training for non-ambulatory children with spastic cerebral palsy - Xia, Beier; Mi, Na; Wen, Zhixiang; Zhang, Yang (Frontiers in Neurology, 2025)
PurposeChildren with spastic cerebral palsy (CP) classified as Gross Motor Function Classification System (GMFCS) level IV face profound mobility limitations and are often excluded from intensive gait rehabilitation programs due to the severity of their impairments. Robotic-assisted gait training offers a promising avenue for functional improvement in this underserved population, yet empirical evidence remains scarce. This protocol describes a trial designed to evaluate the effects of a 6-month robotic gait training intervention on gross motor function, walking capacity, joint range of motion, muscle morphology, and psychological satisfaction in children with GMFCS level IV CP. Results will be reported in a subsequent publication following trial completion.MethodsThis two-arm, parallel-group, randomized controlled trial will enroll 36 children aged 6–12 years with GMFCS level IV CP. Participants will be randomized 1:1 to either the intervention group (robotic gait training using the RoboCT Pediatric Lower Limb Rehabilitation Robot) or the control group (usual care as determined by family preference). The intervention group will receive 45-min sessions, three times per week for 24 weeks. Primary outcomes include Gross Motor Function Item Set and walking capacity (1-min walk test). Secondary outcomes include passive ankle joint range of motion, lower-limb muscle morphology via ultrasound, and psychological satisfaction. Linear mixed-effects models will evaluate group-by-time effects under an intention-to-treat framework.DiscussionThis will be one of the first trials to explore long-term robotic gait training in children with GMFCS level IV CP. Findings may inform evidence-based rehabilitation approaches and improve access to technology-supported interventions in this highly underserved population.Clinical trial registrationClinicalTrials.gov, NCT07049523.